﻿Four new species and two newly recorded species of Limacodidae (Lepidoptera, Zygaenoidea) from China - Jun Wu; Alexey V. Solovyev; Hui-Lin Han (ZooKeys, 2022)
Four new species, Kitanola shilinensis sp. nov., K. eleganta sp. nov., Fignya ravalba sp. nov., and Euphlyctinides pseudolaika sp. nov., are described from southwestern China. Two species are reported new to China, Euphlyctinidis indi Solovyev, 2009 and Limacocera pachycera (Hampson, 1897). The adults and genitalia of all the treated species are illustrated. A checklist for the species belonging to the treated genera is provided.